(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India has had a sharp increase in the estimated number of HIV infections, from a few thousand cases in the early 1990s to around 5.1 million people living with HIVAIDS today. With a population of over one billion, the HIV epidemic in India will have a major impact on the overall spread of HIV in Asia and the Pacific, and worldwide. This article discusses the impact of a mass media entertainment-education campaign to prevent HIVAIDS. This review systematically examined the effectiveness of 24 mass media interventions on changing human immunodeficiency virus (HIV)-related knowledge, attitudes and behaviors. Human resource capacity building is a key strategy in the design, delivery, sustainability and scale up HIV treatment and prevention programmes. The review aims to present human resource capacity building initiatives undertaken by the National AIDS Control Organization (NACO) and to discuss the available opportunities in India.Various opportunities to enhance and consolidate capacity building responses in HIVAIDS in India may include mainstreaming of capacity building, appropriate management of knowledge and resources, effective delivery of training. measuring and documenting impact, accreditation of programme and institutes, use of information technology, identifying and implementing innovations and working for sustainability.Growing demand for capacity-building in HIVAIDS needs substantial efforts to ensure that these are implemented effectively and efficiently. NACO had made significant strides in these regards, but at the same time there are arduous challenges like measuring impact, quality, documentation, operational research, and sustainability. This review will provide feedback to the NACO for strengthening its strategic document for human resource capacity building.